ANALYSIS OF AGREEMENT MARRIAGE ISLAMIC POPULATION CASE IN INDONESIA - Beby Sendy (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
In this time some of the peoples Indonesia before marriage was preceded by the making of marriage agreements among prospective grooms and women. The marriage agreement as an often also referred to as a pre-marriage agreement or prenuptial agreement that agreements made before marriage take place and binding the two sides of the bride and married woman candidates. A legal arrangement in the case of a marriage agreement is contained in Article 29 of Law no. 1 of 1974 concerning Marriage, Articles 47 to 52 of KHI and also in Articles 139 to Article 154 of the Civil Code. Islamic law does not set explicitly in marriage agreements. However, based on the Qur'an and Hadith no single verse prohibits the making of marriage legally approval as long as it is not contrary to Islamic Shari'a and the marriage agreement is beneficial to the couple husband and wife. Thus, Islamic law justifies the implementation of marriage agreements among Islamic citizens. Among potential married couples aged over 25 years old up to 40 years past and have education level between D3 to S1 know and understand the purpose and benefits of the marriage agreement, but because it is not obligated in Islamic law hence not implemented marriage agreement among Muslim citizen.